The Application and Outcomes of Nigerian Education: A Philosophical Perspective - Berebon, Charles (Indonesian Journal of Educational Studies, 2022)
The progress and success of a country are heavily reliant on the formulation and enforcement of suitable education legislation. Therefore, governments worldwide prioritise educational programmes as tools for national growth. In Nigeria, issues in implementing education policies hinder academic performance despite their perceived relevance. The report used secondary sources such as existing literature and document reviews to identify institutional inadequacies, a lack of expertise, and insufficient personnel as key constraints to education policy development in Nigeria. This hindered the attainment of educational policy objectives. It is advised to enhance institutional capacity, attract competent and qualified individuals, and ensure full engagement of eligible stakeholders in educational establishments. This is thought to significantly help in creating high-quality educational policies and executing them efficiently to achieve academic achievement.